Muscle Strength and Balance Training in Sarcopenic Elderly: A Pilot Study with Randomized Controlled Trial. (January 2013) - Bellomo, R.G.; Iodice, P.; Maffulli, N.; Maghradze, T.; Coco, V.; Saggini, R.
In aging, there is a gradual decrease in muscle mass (sarcopenia) and muscle strength which contributes to a decline in physical functions, increased disability, frailty, and loss of independence. Physical activity can reduce functional decline due to aging. Randomized controlled trials (RCT) are needed to determine the effectiveness of different exercise stimuli on muscle strength and balance in the sarcopenic elderly. Forty male volunteers diagnosed with sarcopenia (CDCP) (70.9±5.2yrs) were enrolled in this study. A randomized, controlled trial, with blind assessment, was designed to study the effect of global sensorimotor, high intensity focused vibrational (intensity: 300Hz) and resistance training (intensity: 60–80% of maximum theoretical force, 10–12 repetitions for 3 sets) stimuli on muscle strength and balance confidence. The subjects were randomly assigned to three different training programs or a control group which was encouraged to maintain their habitual activity level. The training was performed for 12 weeks in all groups: 2 sessions/week in Gsm and Ret groups; 1 session/week for the first 8 weeks and 3 sessions/week for the last 4 weeks in Vam group. The main outcome was maximal force contraction of the lower limbs, and secondary outcomes were static and dynamic balance confidence. All the training regimens increased isometric strength. Both the sensorimotor and the vibrational training increased stability with a reduction of sway area and of ellipse surface (p<0.01). Gait analysis showed a significant increase in the length of the half-step in all three groups (respectively 108%, p <0.01; 92% p< 0.01; 65% p <0.05). AH the training programs implemented in the present investigation increase muscle strength. In addition, sensorimotor and vibrational training intervention aims to transfer these peripheral gains to the functional and more complex task of balance, in order to reduce the risk of falls.